Current Challenges and Future Perspectives of Renal Tubular Dysfunction in Diabetic Kidney Disease - Duan, Suyan; Lu, Fang; Song, Dandan; Zhang, Chengning; Zhang, Bo; Xing, Changying; Yuan, Yanggang (Frontiers in Endocrinology, 2021)
Over decades, substantial progress has been achieved in the understanding of proteinuria pathogenesis in DKD, biomarkers for DKD screening, diagnosis, and prognosis, novel hypoglycemia agents in clinical trials, rendering more attention focused on the role of renal tubules in DKD. Previous studies have demonstrated that morphological and functional changes in renal tubules are highly involved in the occurrence and development of DKD. Novel tubular biomarkers have shown some clinical importance. However, there were remain many challenges in transition into personalized diagnosis and guidance for individual therapy in clinical practice. The clinical relevance of increased proximal reabsorption and hyperfiltration in diabetes is suggested by the ability of sodium-glucose cotransporter-2 (SGLT2) to improve renal outcomes in diabetic patients in large-scale clinical trials, further promoting the emergence of renal tubulocentric researches. Therefore, this review examines the recent progress in the pathophysiology associated with involved mechanisms of renal tubules, potential tubular biomarkers with clinical application, and the contribution of renal tubular factors in DKD management. The mechanism of kidney protection and impressive results of clinical trials in SGLT2 inhibitors are summarized and discussed which oﬀers a comprehensive update of therapeutic strategies targeting renal tubules.